2007
DOI: 10.1093/ageing/afl165
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial and functional mobility assessment tools for fall risk among older adults in community, home-support, long-term and acute care settings

Abstract: fall-risk assessment tools exist that show moderate to good validity and reliability in most health service delivery areas. However, few tools were tested more than once or in more than one setting. Therefore, no single tool can be recommended for implementation in all settings or for all subpopulations within each setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
235
0
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(260 citation statements)
references
References 42 publications
3
235
0
10
Order By: Relevance
“…Furthermore, a study by Scott et al [33] found that only few tools have been investigated more than once or in more than one setting. According to the authors, no single tool could, therefore, be recommended for use in all settings or for multiple sub-populations within each setting [33]. These findings suggest that current clinical motor performance tests may possess limitations as tools for subject-specific fall risk assessment.…”
Section: Deficits In Common Testsmentioning
confidence: 99%
“…Furthermore, a study by Scott et al [33] found that only few tools have been investigated more than once or in more than one setting. According to the authors, no single tool could, therefore, be recommended for use in all settings or for multiple sub-populations within each setting [33]. These findings suggest that current clinical motor performance tests may possess limitations as tools for subject-specific fall risk assessment.…”
Section: Deficits In Common Testsmentioning
confidence: 99%
“…28,29 In this study, participants were timed from the moment they were instructed to stand up from a chair (seat height ¼ 48 cm), walk at their preferred usual pace for 3 m, turn around, and walk back to sit in the chair. Participants were allowed to use the arms of the chair to stand up and to use their usual mobility aid, if any.…”
Section: Timed Up-and-go Testmentioning
confidence: 99%
“…The Hendrich II Fall Risk Model score is one of many fall risk assessment tools designed to identify patients at risk for falls. 14,15 intErvEntion Our intervention consisted of adding a physician fall risk assessment for all patients at admission to the neurology unit. Physicians were instructed to make this judgment on the basis of their usual admission history taking and physical examination and were blinded to the nursing fall risk assessment.…”
Section: Existing Fall Risk Assessment Processmentioning
confidence: 99%